THE CONTRIBUTION OF PHILOSOPHY AND EPISTEMOLOGY TO THE IMPLEMENTATION OF A HEALTHCARE CYBERSECURITY POLICY - DENIS, Christophe (MEDECINE LEGALE DROIT MEDICAL, 2025)
Implementing a cybersecurity policy in healthcare requires users to be made aware of a set of rules to avoid creating vulnerabilities in the digital system. In order to prevent users from becoming passive, it is important to ensure that compliance with a comprehensive set of rules does not restrict their individual agency and make them more vulnerable to alienation. This would deprive the system of the opportunity to take advantage of the human factor, i.e. the use of cognitive shortcuts to solve complex problems quickly. The human factor has been the subject of numerous studies in cognitive psychology, exploring the way in which individuals interact with their environment, whether in system design, training or security. We propose to integrate concepts from philosophy and epistemology into the development of health cybersecurity. Firstly, we will analyse the epistemological issues linked to the increasingly widespread use of learning methods by measuring the impact of this technique on the Platonic relationship between téchnè (art, technique) and épistemê (knowledge). Finally, we present the foundations of our work on defining a hybrid mode of communication between users and the machine, particularly if a conversational agent is used, in order to limit the risks of addiction and loss of meaning induced by the Eliza effect. The Eliza effect refers to the unconscious tendency to assimilate the behaviour of a computer to that of a human being.